Experiências desacatam referências?: poéticas problemáticas para a criação em teatro - Machado, Nicolle Silva (2020)
Contemporary modes of scenic creation recreate techniques and seek strength in the sensitive materials of its actors with a view to an increasingly pulsating scene. These processes deal with games and exercises that trigger repertoires and desires for creation, but is it possible to stimulate environments that make bodies available to experience and reach the realities of the process as major referents? This research addresses practical aspects of theater creation, raising problems about procedural references and their disfigurement movement in the face of the experience of the actors. Through investigation-creation, it proposes fertile attitudes to the event, suspecting common terms while establishing procedures for mapping problems, references, themes and circumscribing a dramaturgy of the creative process that manifests itself in the scene, blurring the conventions of theatrical representation. With practical steps of immersion in creative studios in two shows: Pacto (2017) and A Vagabunda (2020), the research develops tracing relationships between the desires for creation, the experience and the images that emerge from the creative process as an encounter